2007
DOI: 10.21273/hortsci.42.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time of Harvest on Postharvest Leaf Abscission in Lantana (Lantana camara L. ‘Dallas Red’) Unrooted Cuttings

Abstract: This study investigated the preharvest carbohydrate status and postharvest ethylene action of unrooted shoot-tip cuttings of lantana ‘Dallas Red’ harvested at three times during the day (0800, 1200, and 1600 hr) in relation to subsequent leaf abscission, shoot apices blackening, and adventitious root formation. The cuttings harvested at various times during the day were stored in darkness at 20 ± 1 °C for 4 days in sealed polyethylene bags. The cuttings harvested at 0800 hr<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…Sucrose levels increased from morning to noon in leaves of all tested species but then decreased for afternoon-harvested stems. A similar response has also been reported by Rapaka et al (2007) for shoot-tip cuttings of lantana and leaves of sugar beet (Beta vulgaris L.) by Fondy and Geiger (1982). Fructose levels of all three species were higher in morningharvested stem tissues and noon-or afternoonharvested leaves and petals immediately after harvest, which was mobilized to petals during storage.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Sucrose levels increased from morning to noon in leaves of all tested species but then decreased for afternoon-harvested stems. A similar response has also been reported by Rapaka et al (2007) for shoot-tip cuttings of lantana and leaves of sugar beet (Beta vulgaris L.) by Fondy and Geiger (1982). Fructose levels of all three species were higher in morningharvested stem tissues and noon-or afternoonharvested leaves and petals immediately after harvest, which was mobilized to petals during storage.…”
Section: Discussionsupporting
confidence: 84%
“…These findings can assist cut flower growers to extend vase life by rescheduling the time stems are harvested during the day. Similar improvements in shelf life of sweet basil (Lange and Cameron, 1994), baby salad (Clarkson et al, 2005), broccoli (Hasperué et al, 2011), and unrooted shoot-tip cuttings of lantana (Rapaka et al, 2007) were observed when harvested later in the day.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…(croton), Pelargonium •hortorum Bailey (pro sp.) [inquinans • zonale] (zonal geranium), and Lantana camara L. (lantana) as reported by M€ uller et al (1998), Kadner et al (2000), and Rapaka et al (2007), respectively.…”
supporting
confidence: 58%